Environmental performance and international trade and its indicators for the Arab States of the year 2008 - Najlaa Edrees AL-Abasi; Ahmed Tarik AL-aga; Saad Mahmood AL-Kawas (دراسات أقليمية, 2010)
Part of the Arab countries made significant efforts to preserve on the environment through the protection of natural resources, The main problem in this study represented in the answer on the following questions: are there disparities in key indicators of environmental performance of those States, what are the causes and appropriate solutions to that This paper identifies the main indicator of environment performance in Arab states, The study falls into two parts the first one focuses on the theoretical frame of the environment in the framework of free trade while the second part deals with the indicators of the development in the environment performance in the Arab states.